Toward a Research Agenda for the Study of Situation Perceptions: A Variance Componential Framework. (August 2019) - Rauthmann, John; Sherman, Ryne
Situation perception represents the fulcrum of a "psychology of situations" because situation ratings are ubiquitous. However, no systematic research program exists so far, particularly because two competing traditions have not been integrated: Objectivist views stress situations' consensually shared meanings (social reality), and subjectivist views idiosyncratic meanings (personal reality). A componential framework can disentangle social from personal reality in situation perceptions: When multiple perceivers (P) rate multiple situations (S) on multiple situation characteristics (C), variance in those ratings can be decomposed according to S × C, P × S, and P × C breakdowns. Six grand questions of situation perception research are spawned from these decompositions: complexity, similarity, assimilation, consensus, uniqueness, and accuracy. Analyses of real data are provided to exemplify our ideas, along with customizable R codes for all methods. A componential framework allows novel and unique insights into different questions surrounding situation perceptions and provides a coherent research agenda.